IMPLEMENTASI KEBIJAKAN JAM MALAM BAGI PESERTA DIDIK DALAM UPAYA PEMBENTUKAN GENERASI PANCA WALUYA DI PURWAKARTA - Mukti, Saepul; Fikri Rafsanjani, Mohammad; Muhammad Fasya, Nizar; Hasanah, Aan; Samsul Arifin, Bambang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The curfew policy for students is a strategic initiative by the Purwakarta Regency Government to support the development of the Panca Waluya generation, as mandated by the Circular Letter of the Governor of West Java Number 51/PA.03/DISDIK and reinforced by the Circular Letter of the Regent of Purwakarta Number 100.3.4/916-Disdik/2025. This study aims to explore the process of implementing the student curfew policy, stakeholder responses, and the challenges encountered in its local execution. The research method employed is a descriptive qualitative approach with a case study design. Data collection techniques include interviews, observations, and document analysis. The data were analyzed using Miles and Huberman’s interactive model, consisting of data collection, data reduction, data display, and conclusion drawing/verification. The results show that the policy implementation has received support from most stakeholders, but it faces challenges in terms of supervision, cross-sectoral coordination, and public dissemination. The findings imply the need to strengthen the role of village task forces (Satgas Desa), integrate school and community programs, and adopt a cultural approach to supervision to ensure the effectiveness of the policy in shaping student character that aligns with the values of Cageur, Bageur, Bener, Pinter, and Singer.